Effects of adrenomedullin on systolic and diastolic myocardial function - Ana Patricia Fontes Sousa (2009)
Adrenomedullin (AM) effects were studied in rabbit papillary muscles by adding increasing concentrations (10(-10) to 10(-6) M) either alone or after pre-treatment with L-NNA, indomethacin, AM22-52 (AM receptor antagonist), CGRP(8-37) (CGRP receptors antagonist), KT5720 (PKA inhibitor), as well as after endocardial endothelium (EE) removal. Passive length-tension relations were constructed before and after a single concentration of AM (10(-6) M). AM concentration-dependently induced negative inotropic and lusitropic effects, and increased resting muscle length (RL). At 10(-6) M, AT, dT/dt(max) and dT/dt(min) decreased 20.9 +/- 4.9%,18.3 +/- 7.3% and 16.7 +/- 7.8%, respectively, and RL increased to 1.010 +/- 0.004 L/L(max). Correcting RL to its initial value resulted in a 26.6 +/- 6.4% decrease of resting tension, indicating decreased muscle stiffness, also patent in the down and rightward shift of the passive length-tension relation. The negative inotropic effect of AM was dependent on its receptor, CGRP receptor, PKA, the EE and NO, while the effects of AM on myocardial stiffness were abolished by EE damage and NO inhibition. This latter effect represents a novel mechanism of acute neurohumoral modulation of diastolic function, suggesting that AM is an important regulator of cardiac filling.